(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The contribution sums up a funded project that came to an end in the present year. The project has been focused on forms of welfare before welfare, i.e. public assistance in the medieval and early modern age. The paper lists the starting assumptions, the objectives achieved, the results of the surveys carried out, and the prospects for further development.